Peran Penjamin Mutu Internal dengan Sekolah Unggul: (Studi Kasus: SMP N 2 Tarutung) - Mei Manullang; Riamin Sinaga; Andar Gunawan Pasaribu (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to analyze the role of Internal Quality Assurance (IQA) in creating and maintaining excellent schools. IQA is a systematic mechanism designed to ensure that all educational processes operate according to established quality standards while serving as a means for continuous evaluation and improvement. This research employs a literature study method with a descriptive qualitative approach, utilizing secondary sources such as books, scientific journals, government regulations, and relevant previous studies. The findings indicate that IQA plays a strategic role in building an education system oriented toward quality and accountability. Through the implementation of the Plan-Do-Check-Act (PDCA) cycle, schools are able to establish measurable quality standards, control learning processes, and conduct continuous evaluations of educational outcomes. The implementation of IQA also fosters a culture of quality that encourages collective awareness among all school members regarding the importance of continuous improvement. However, IQA implementation still faces several challenges, including limited competent human resources, lack of leadership commitment, inadequate facilities and infrastructure, and resistance to change. A case study at SMP Negeri 2 Tarutung reveals that the success of IQA is determined by visionary leadership, stakeholder support, and the use of data-based quality information systems. Therefore, IQA functions not only as a supervisory tool but also as a managerial strategy for achieving holistic and sustainable educational quality improvement